Galileo goes to jail : and other myths about science and religion - Numbers, Ronald L. (Cambridge, Mass. : Harvard University Press, 2009)
Ronald Numbers has recruited the leading scholars in this new history of science to puncture the myths, from Galileo's incarceration to Darwin's deathbed conversion to Einstein's belief in a personal God who "didn't play dice with the universe." The picture of science and religion at each other's throats persists in mainstream media and scholarly journals, but each chapter in Galileo Goes to Jail shows how much we have to gain by seeing beyond the myths. --from publisher description.
That the rise of Christianity was responsible for the demise of ancient science / David C. Lindberg -- That the medieval Christian church suppressed the growth of science / Michael H. Shank -- That medieval Christians taught that the earth was flat / Lesley B. Cormack -- That medieval Islamic culture was inhospitable to science / Syed Nomanul Haq -- That the medieval church prohibited human dissection / Katharine Park -- That Copernicanism demoted humans from the center of the cosmos / Dennis R. Danielson -- That Giordano Bruno was the first martyr of modern science / Jole Shackelford -- That Galileo was imprisoned and tortured for advocating Copernicanism / Maurice A. Finocchiaro -- That Christianity gave birth to modern science / Noah J. Efron -- That the scienfitic revolution liberated science from religion / Margaret J. Osler -- That Catholics did not contribute to the scientific revolution / Lawrence M. Principe -- That René Descartes originated the mind-body distinction / Peter Harrison -- That Isaac Newton's mechanistic cosmology eliminated the need for God / Edward B. Davis -- That the church denounced anesthesia in childbirth on biblical grounds / Rennie B. Schoepflin -- That the theory of organic evolution is based on circular reasoning / Nicolaas A. Rupke -- That evolution destroyed Darwin's faith in Christianity : until he reconverted on his deathbed / James Moore -- That Huxley defeated Wilberforce in their debate over evolution and religion / David N. Livingstone -- That Darwin destroyed natural theology / Jon H. Roberts -- That Darwin and Haeckel were complicit in Nazi biology / Robert J. Richards -- That the Scopes trial ended in defeat for antievolutionism / Edward J. Larson -- That Einstein believed in a personal God / Matthew Stanley -- That Quantum physics demonstrated the doctrine of free will / Daniel Patrick Thurs -- That "intelligent design" represents a scientific challenge to evolution / Michael Ruse -- That creationism is a uniquely American phenomenon / Ronald L. Numbers -- That modern science has secularized Western culture / John Hedley Brooke.
Includes bibliographical references (pages 235-284) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Master record variable field(s) change: 072
Keywords: Science -- History; Scientists -- History; Religion and science -- History; Religion and state -- History; RELIGION -- General; Religion and science; Religion and state; Science; Scientists; Naturwissenschaften; Religion; Naturwissenschaften; Religion; Vetenskap -- historia; Religion och vetenskap; Kristendom och vetenskap; SCIENCE / History; Geschichte; Electronic books; History